Systems Thinking and Question-based Learning Management - Hankuttum, Chuthathip; Selosreechai, Somphanthushthorn; Khanewan, Prachan (Interdisciplinary Academic and Research Journal, 2023)
Nowadays, Thai education circles attach great importance to the teaching and learning of thinking skills. This can be seen from educational policies that focus on critical thinking skills to encourage learners to achieve student-centered learning. System Thinking is an important skill in the 21st century. Today's world has changed from the past to a world where technology has improved. Therefore, developing the ability to think in System Thinking is necessary for the education of the 21st-century world. Therefore, teaching methods should be found that can promote learning methods, the learners' thinking processes, and problem-solving skills appropriately. However, question-based learning is an important starting point to develop learners towards systems thinking skills. Question-based learning is an important tool for stimulating learning in 21st-century learners, in which learning must stimulate the brain to work and practice all the time, using thinking, analyzing, Memorizing information, and neural connections, which increases the brain's ability to develop. The question-based learning process for systems thinking skills includes; Step 1:Create Question. Step 2: Question to curiousness. Step 3: Question to the conversation. Step 4: Question to check. Step 5:Question to conclude. And Step 6: Question to continue.